Polymer Binder BioCo3 with Silicates and its Application to Microwave-Cured Moulding Sand - Grabowska B.; Kaczmarska K.; Bobrowski A.; Drożyński D.; Żymankowska-Kumon S.; Cukrowicz S. (Archives of Foundry Engineering, 2017)
The effects of silica additive (Poraver) on selected properties of BioCo3 binder in form of an aqueous poly(sodium acrylate) and dextrin (PAANa/D) binder were determined. Based on the results of the thermoanalytical studies (TG-DTG, FTIR, Py-GC/MS), it was found that the silica additive results in the increase of the thermostability of the BioCo3 binder and its contribution does not affect the increase in the level of emissions of organic destruction products. Compounds from group of aromatic hydrocarbons are only generated in the third set temperature range (420-838°C). The addition of silicate into the moulding sand with BioCo3 causes also the formation of a hydrogen bonds network with its share in the microwave radiation field and they are mainly responsible for maintaining the cross-linked structures in the mineral matrix system. As a consequence, the microwave curing process in the presence of Poraver leads to improved strength properties of the moulding sand (Rum). The addition of Poraver's silica to moulding sand did not alter the permeability of the moulding sand samples, and consequently reduced their friability. Microstructure investigations (SEM) of microwave-cured samples have confirmed that heterogeneous sand grains are bonded to one another through a binder film (bridges).